2019
DOI: 10.1158/1541-7786.mcr-17-0636
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Epigenetic and Gene Expression Analysis of Renal Tumor Progression to Metastasis

Abstract: The Cancer Genome Atlas (TCGA) and other large-scale genomic data pipelines have been integral to the current understanding of the molecular events underlying renal cell carcinoma (RCC). These data networks have focused mostly on primary RCC, which often demonstrates indolent behavior. However, metastatic disease is the major cause of mortality associated with RCC and data sets examining metastatic tumors are sparse. Therefore, a more comprehensive analysis of gene expression and DNA methylome profiling of met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 59 publications
0
43
0
Order By: Relevance
“…As a positive control, we identified increased 5mC enrichment in RCC (as compared with matched normal kidney) of the promoter of ESSRG , a gene that we recently reported to be methylated in RCC (Fig. S2, B and C; Nam et al, 2019). Collectively, these data demonstrate that the PRDM16 promoter region is methylated in RCC.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…As a positive control, we identified increased 5mC enrichment in RCC (as compared with matched normal kidney) of the promoter of ESSRG , a gene that we recently reported to be methylated in RCC (Fig. S2, B and C; Nam et al, 2019). Collectively, these data demonstrate that the PRDM16 promoter region is methylated in RCC.…”
Section: Resultsmentioning
confidence: 88%
“…As noted previously, PRDM16 has a prominent role in brown fat metabolism and has previously been shown to induce expression of the mitochondrial metabolism-related transcription factors in adipocytes including PGC-1α and ERR-γ (encoded by PPARGC1A and ESRRG ) as well as uncoupling protein 1 ( UCP1 ; Kajimura et al, 2008; Seale et al, 2007, 2008). Notably, the expression of PPARGC1A and ESRRG has previously been shown to be reduced in RCC (LaGory et al, 2015; Nam et al, 2019). We therefore assessed the effects of PRDM16 on the expression of these factors in RCC cells via stable transduction in RCC cells.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, several promoter-methylated genes involved in the various hallmarks of cancer are found in RCC, including the ones related to angiogenesis (in which VHL is included), metabolism, apoptosis and cell cycle, among others [95]. Agents targeting specific epigenetic aberrations have also shown anti-neoplastic activity in RCC, including the EZH2 inhibitor GSK126, which suppressed migration and invasion [96], and various HDAC inhibitors, alone or in combination with routinely used agents [97][98][99][100][101]. Moreover, similar to BlCa, these latter inhibitors also showed the ability to reverse resistance to currently used agents such as mTOR inhibitors [102].…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 99%
“…Similar to its role in female tumors, ESRRG has been reported to be a tumor suppressor in prostate cancer, a male cancer, inducing p21 and p27 expression to arrest the cell cycle . Recently, Nam et al reported that ESRRG plays a canonical role in renal cell carcinoma (RCC). The study found that ESRRG loss occurred via DNA methylation and histone repressive silencing mediated by the polycomb repressor complex 2 (PRC2), and ESRRG restoration in RCC lines suppressed the migratory and invasive phenotypes.…”
Section: Discussionmentioning
confidence: 99%